A More but not Fully Constructed Arena: A Critical Analysis of the AKP’s Policy toward Kurdish Ethno-Cultural Rights (2002-2014) - Kolcak, Hakan (The Age of Human Rights Journal, 2015)
Until the very early 2000s, the Kurds had suffered from numerous Turkification policies; however, after the Justice and Development Party (Adalet ve Kalkınma Partisi, AKP) came into power in 2002, a new political process aimed at enhancing Kurdish ethno-cultural rights was initiated. As a result of this process, the historical harm done by the early republican regime, the three military administrations and their successor governments has been reduced. Notwithstanding, there are still some restrictions that can be removed through a new constitutional reform package. By employing the methods of comparative politics and constitutional law, this article gives the following suggestions for the reform package. First, in the name of laying a foundation for bilingual education, the reform package may delete or amend Article 42(9) of the Turkish Constitution, according to which the Kurds are now obliged to receive education in Turkish, hindering them from being taught in their mother tongue. Second, it may revise Article 3(1) of the Constitution, under which Turkish is the sole language of the state. The new version of Article 3(1) may recognise the Kurdish language and its dialects as national or regional official languages. Finally, the constitutional reform package may expand the scope of Article 134, pursuant to which only Turkish cultural, historical and linguistic features can now receive public funding and be protected constitutionally, and it may grant the same privilege to Kurdish characteristics.